2019
DOI: 10.2174/1871520619666190731162722
|View full text |Cite
|
Sign up to set email alerts
|

Celastrus Orbiculatus Extracts Inhibit the Metastasis through Attenuating PI3K/Akt/mTOR Signaling Pathway in Human Gastric Cancer

Abstract: Background: Rapamycin receptor inhibitors have been applied in the clinic and achieved satisfactory therapeutic effect recently. The mechanisms did not clearly show how the Celastrus orbiculatus Extracts (COE) inhibited the expression of the mammalian Target of Rapamycin (mTOR) in human gastric cancer cells. The aim of this study was to investigate whether the COE inhibited the metastasis through the mTOR signaling pathway in human gastric cancer MGC-803 cells. Methods: The abnormal expression level of mTOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As shown in Figure 3A, uorescence analysis showed that BBD treatment severely disrupted cell morphology. Western blot analysis demonstrated that BBD treatment highly induced autophagy-related signals of LC3 I/II and Beclin 1, but suppressed p62, leading to autophagy in SGC7901/DDP cells ( Figure 3E and 3F) Activation of the PI3K/AKT/mTOR signaling pathway has been shown to have carcinogenic effects in gastric cancer, and its regulatory pathways are closely related to genetic variation, cell proliferation, migration, invasion, cell cycle, apoptosis, autophagy, angiogenesis, multi-drug resistance and cell viability [21,[39][40][41][42][43][44][45][46]. Guo et al found that Ubenimex inhibited the phosphorylation and activation of the PI3K/AKT/mTOR pathway and down-regulated membrane transporter (such as p-gp and MRP1) expression, resulting in the intracellular accumulation of 5-uorouracil and oxaliplatin [47].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 3A, uorescence analysis showed that BBD treatment severely disrupted cell morphology. Western blot analysis demonstrated that BBD treatment highly induced autophagy-related signals of LC3 I/II and Beclin 1, but suppressed p62, leading to autophagy in SGC7901/DDP cells ( Figure 3E and 3F) Activation of the PI3K/AKT/mTOR signaling pathway has been shown to have carcinogenic effects in gastric cancer, and its regulatory pathways are closely related to genetic variation, cell proliferation, migration, invasion, cell cycle, apoptosis, autophagy, angiogenesis, multi-drug resistance and cell viability [21,[39][40][41][42][43][44][45][46]. Guo et al found that Ubenimex inhibited the phosphorylation and activation of the PI3K/AKT/mTOR pathway and down-regulated membrane transporter (such as p-gp and MRP1) expression, resulting in the intracellular accumulation of 5-uorouracil and oxaliplatin [47].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, multiple GC cell lines (MGC-802, BGC-823, AGC) have been applied in previous research to investigate the effect of COE treatment on the growth, invasion, and metastasis of GC. 63 - 65 Relevant results indicated that COE could effectively inhibit the growth, invasion, and metastasis of GC in different GC cell lines, which may be able to partially compensate the lack of study. At present, our research group is isolating and identifying CSC-like cells using the HGC-27 cell line to explore the effect of COE on the differentiation of GCSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway has been identified to play an important role in the progression of various cancer types, including GC (27)(28)(29). Once the PI3K/AKT signaling pathway is activated, phosphorylation of AKT directly regulates the expression of a range of proteins involved in cell metabolism, proliferation, motility, invasion and migration.…”
Section: Discussionmentioning
confidence: 99%